Pengaruh Pendidikan Etika Bisnis Dan Religiusitas Terhadap Persepsi Etis Mahasiswa Akuntansi Di Indonesia : Pendekatan Tinjauan Literatur (International Forum of Researchers and Lecturers, 2024)
This research aims to investigate the influence of business ethic and religiosity on the perception of accounting students in Indonesia. The research methodology adopts a systematic approach to extract data from nine relevant articles throught Google Scholar search. Business ethic and religiosity have a positive impact on student’s ethical perception. The results indicate that out of the accumulated 9 articles, one research method was employed, namely quantitative. Among the 9 articles, 7 factors were identified as influencing the ethical perception of accounting students in Indonesia, including business ethic education, religiosity, love of money, Machiavellianism, equity sensitivity, understanding of accountant’s code of ethic, and emotional intelligence.